Membangun Genuine Hospitality: Studi Tentang Pengalaman Perempuan Indonesia dalam Industri Kapal Pesiar Global - Gloria Nancyska Mourina; Emmelia Nadira Satiti; Titik Akiriningsih (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study explores the experiences of Indonesian women working in the global cruise ship industry and how they contribute to the creation of genuine hospitality. Using a qualitative interpretive phenomenology approach, the research focuses on solidarity, informal leadership, mentorship, empowerment, and competence development. Data were collected through in-depth interviews with 15 Indonesian female workers across five international cruise brands. The findings show that solidarity among workers provides emotional support and practical guidance, which further develops informal leadership through mentorship. These processes empower women to gain confidence, improve technical and interpersonal skills, and strengthen their professional competence. As a result, they are able to deliver authentic and empathetic service, which reflects the concept of genuine hospitality. The study concludes that solidarity and empowerment are key factors in shaping women’s capacity to adapt and succeed in multicultural cruise ship environments. This research contributes to tourism and hospitality studies by highlighting the role of social capital and informal leadership in enhancing service quality, and offers insights for cruise companies, training institutions, and vocational education programs.